Associations of C1q/TNF-Related Protein-9 Levels in Serum and Epicardial Adipose Tissue with Coronary Atherosclerosis in Humans. (17th September 2015) - Wang, Jing; Hang, Tao; Cheng, Xun-min; Li, De-min; Zhang, Qi-gao; Wang, Li-jun; Peng, Yong-ping; Gong, Jian-bin
Abstract : Objective . To investigate the correlation of CTRP9 with coronary atherosclerosis. Methods . Coronary angiography confirmed CAD in 241 patients (62 received CABG) and non-CAD in 121 (55 received valve replacement). Results . Serum levels of LDL-C, CRP, TNF- α, IL-6, and leptin in CAD patients were significantly higher than those in non-CAD patients (P < 0.05 ), but APN and CTRP9 were lower (P < 0.05 ). Serum levels of CTRP9 and APN were negatively related to BMI, HOMA-IR, TNF- α, IL-6, and leptin but positively to HDL-C (P < 0.05 ) in CAD patients. After adjustment of APN, CTRP9 was still related to the above parameters. Serum CTRP9 was a protective factor of CAD (P < 0.05 ). When compared with non-CAD patients, leptin mRNA expression increased dramatically, while CTRP9 mRNA expression reduced markedly in epicardial adipose tissue of CAD patients (P < 0.05 ). The leptin expression and macrophage count in CAD group were significantly higher than in non-CAD group, but CAD patients had a markedly lower CTRP9 expression (P < 0.05 ). Conclusions . Circulating and coronary CTRP9 plays an important role in the inflammation and coronary atherosclerosis of CAD patients. Serum CTRP9 is an independent protective factor of CAD.